EFEKTIVITAS PENGGUNAAN ALOKASI DANA DESA DALAM PENYUSUNAN RENCANA KERJA PEMBANGUNAN DI DESA LOMBONG KECAMATAN MALUNDA KABUPATEN MAJENE - Nur Fitrah; Ainal Mardiah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2019)
This study aims to obtain an overview of the effectiveness of the use of Village Fund Allocation in the preparation of development work plans in the Lombong Village, Malunda District, Majene Regency. Data collection is carried out using technical field research, library research and data tracking. Qualitatively analyzed by describing and explaining data obtained from the field. The results showed that the use of village fund allocations in the preparation of village development work plans in the village of Lombong had not been running optimally because there were several obstacles including; limited manager HR capabilities; manager's fees are relatively small; disbursement of ADD funds is often delayed; there are still deductions from individual officers; frequent changes in management and workers; guidance and training is still needed on managing village fund allocations.